Soil fauna and soil functions: a jigsaw puzzle - Briones, María Jesús I. (Frontiers in Environmental Science, 2014)
Terrestrial ecologists and soil modelers have traditionally portrayed the inhabitants of soil as a black box labeled as "soil fauna" or "decomposers or detritivores” assuming that they just merely recycle the deposited dead plant material. Soil is one of the most diverse habitats on Earth and contains one of the most diverse assemblages of living organisms; however, the opacity of this world has severely limited our understanding of their functional contributions to soil processes and to ecosystem resilience. Traditional taxonomy, based on morphological and anatomical aspects, is becoming replaced by rapid processing molecular techniques (e.g. with marker gene-based approaches). However, this may be impracticable in many ecological studies and consequently, the majority of the current knowledge, still contributes little to our understanding of their role in ecosystem functioning. Over the years, different workers have produced several ‘functional classifications’ based on the body width, feeding regime, certain behavioral and reproductive aspects and ecological niches of soil organisms. Unfortunately, the information available is severely restricted to ‘major’ groups. A better physiological and metabolic understanding of when and how a complex community of soil organisms access nutrients, alter their environment and in turn, affect soil processes, will allow a more realistic quantitative evaluation of their ecological roles in the biogeochemical cycles. Here, I review the applicability of the available approaches, highlight future research challenges and propose a dynamic conceptual framework that could improve our ability to solve this functional puzzle.